2017
DOI: 10.1001/jama.2016.21041
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Direct-to-Consumer Advertising and Testosterone Testing and Initiation in the United States, 2009-2013

Abstract: IMPORTANCE Testosterone initiation increased substantially in the United States from 2000 to 2013, especially among men without clear indications. Direct-to-consumer advertising (DTCA) also increased during this time. OBJECTIVE To investigate associations between televised DTCA and testosterone testing and initiation in the United States. DESIGN, SETTING, AND POPULATION Ecologic study conducted in designated market areas (DMAs) in the United States. Monthly testosterone advertising ratings were linked to DMA-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 26 publications
1
49
0
1
Order By: Relevance
“…Advertising is a powerful tool to facilitate disease mongering and foster overdiagnosis, as is shown in the case of Sarafem and others. In the US, direct-to-consumer advertising of testosterone replacement products was associated with testosterone testing and initiation of treatment with testosterone replacement therapy96; many of these cases probably represented overdiagnosis.…”
Section: Related Termsmentioning
confidence: 99%
“…Advertising is a powerful tool to facilitate disease mongering and foster overdiagnosis, as is shown in the case of Sarafem and others. In the US, direct-to-consumer advertising of testosterone replacement products was associated with testosterone testing and initiation of treatment with testosterone replacement therapy96; many of these cases probably represented overdiagnosis.…”
Section: Related Termsmentioning
confidence: 99%
“…In contrast, we were able to assess the effect upon TTh usage of characteristics measured prior to the discontinuation, albeit for a short period of follow‐up and without accounting for the duration of use prior to 2012. Ninety per cent of users self‐reported a testosterone deficiency, but our study did not include data on serum testosterone level monitoring among men before or after TTh initiation, which several studies have documented to be suboptimal . The key strengths of our study are the standardized characterization of TTh use, including participant motivations for use; the large multi‐city sample; and the prospective characterization of demographic, health and socio‐behavioural factors for both HIV‐infected and uninfected participants.…”
Section: Discussionmentioning
confidence: 99%
“…In actuality, only a minority of men who are prescribed testosterone are being properly evaluated for hypogonadism. In a study of men in the United States and United Kingdom, only 14% of men in the United Kingdom and 10% of the men in the United States had more than one testosterone test within 180 days of receiving a prescription for testosterone (28). Another study from the United States showed a similar result, with only 18% of men receiving at least two testosterone tests in the 12 months prior to initiating treatment (29).…”
Section: Testosterone Therapy For Male Hypogonadismmentioning
confidence: 97%
“…In the United States, several pharmaceutical companies launched a highly successful disease awareness campaign for "low T" (28). The goal of this campaign was to increase the rates of testosterone testing and initiation, particularly among middle-and older-aged men, by leading men to believe that androgen deficiency could be a cause of their nonspecific symptoms.…”
Section: Off-label Use Of Testosterone and Advertisingmentioning
confidence: 99%
See 1 more Smart Citation